Interpreting social determinants: Emergent properties and adolescent risk behaviour. - Chris Desmond; Janet Seeley; Candice Groenewald; Nothando Ngwenya; Kate Rich; Tony Barnett (PLoS ONE)
A link between adversity, including low socio-economic status, and behaviours which carry health risks, such as alcohol consumption, has often been observed. The causes of this link are, however, poorly understood, making it difficult to explain why the association is often not linear and why there is so much variability between groups and individuals facing similar adversity. We investigate the use of the concept of emergent properties in explaining the link and its non-linear nature. `Emergent properties' arise from the interaction of factors or items in a high-level system which, as a result, has qualities possessed by none of the individual factors. We apply a mixed methods approach to examine the association of an example emergent property, hope, and alcohol consumption among adolescents in a rural South African site. We found that among adolescents living in similar contexts, there was enough variance in reported levels of hope, that an association with alcohol use could be identified. This result is cause for optimism regarding the potential use of emergent properties in explaining variations in risk behaviour. Improving our measurement of emergent properties is perhaps the biggest challenge facing this approach. More work is needed to take further the task of identifying emergent properties capable of distilling the influence of lower level variables into single measures useful for analysis and policy purposes.